TINDAKAN MENYIMPANG UNTUK MERAIH KEBERMAKNAAN HIDUP: KAJIAN PSIKOANALISIS TOKOH NAYLA DALAM NOVEL NAYLA KARYA DJENAR MAESA AYU - Dara Windiyarti (Balai Bahasa Provinsi Papua, 2019)
This paper aims to reveal the personality changes of Nayla's character in novelNayla. The data source of this research is a novel by Djenar Maesa Ayu publishedby Gramedia Pustaka Utama in 2012. Data collection is done by literary technique.This study uses Karen Horney’s psychoanalysis theory. This paper uses analyticaldescriptive method with psychoanalysis approach. This discussion produces thefollowing. First, relationship disharmonic of parent and children, creating events thatencourage inner conflicts of Nayla’s character. Second, anxieties that underlie innerconflicts trigger the emergence of neurotic behavior in the form of Nayla’s figuresdeviant actions to achieve significance of life.